Sequential Ketene Generation from Dioxane-4,6-dione-keto-dioxinones for the Synthesis of Terpenoid Resorcylates - Barrett,AGM; Elliott,D; Ma,T; Cookson,R; Parsons,P; Selmani,A (Organic Letters, 2016)
Trapping of the ketene generated from the thermolysis of 2-methyl-2-phenyl-1,3-dioxane-4,6-dione-ketodioxinoneat 50 °C with primary, secondary, or tertiary alcohols gave the corresponding dioxinone β-keto-esters in good yieldunder neutral conditions. These intermediates were converted by palladium(0)-catalyzed decarboxylative allyl migration andaromatization into the corresponding β-resorcylates. These transformations were applied to the syntheses of the natural products(±)-cannabiorcichromenic and (±)-daurichromenic acid.